PENILAIAN KINERJA PERBANKAN NASIONAL DENGAN MODEL DISKRIMINAN LINIER - Haryo Satriyawan (Jurnal Riset Akuntansi dan Keuangan, 2005)
Indoqesian eeonomic condition is still unstable. Thi* emerges a very high riskfor bonking to get truubles in ix financial. The national banking which should futtction as the pesent ntles, in the practice, theru are sofrre urrwantes things happen- This unhealthy practice will couse the crisrs in the ndional ban*ing. Finally, this witt c(ruse a decrcase in the health of national banking * , onit". Ow wq to make an assessment ond judgnent about tlu condition of a bank in the futurc based on the finoncial report is by hoving financial report analysis. One of the analysis techniques is financial ratios. The count offinaneiol ratios can be used as a base to develop a prcdiaion model which is usfil a pelict tlp health da bo* in ttoefufi*e" The prediction using c-utof scorc model CAMELfrII be more dang*- ous beceuse the judgww oltlre national banking healtlry by using the CAMEL method in the reseorch is just reprcsented by capital, rentabil-W and liquidity aqrects witlwut counting tle aspects of pruduatve active quality otd manogement. And, the prediction using Hai4 et al. opattting scone, even it has a prcdiction mistake, but it will be more secure or conservative in the prediction because the probobility of an unheaklry bonk to be predicted is more bigger fiom 21 banks, which are as sample, and the probability of a bank to be predicted as a healthy one will be smoller from 2I banks which sanple.Kqtwords : national banking,.linear discriminate model, CAMEL.